ETHICAL LEADERSHIP AND ITS INFLUENCE ON EMPLOYEE RETENTION IN MULTINATIONAL CORPORATION - Susanto, Heri (Penelitian dan Pengembangan Ilmu, 2025)
In the era of globalization, ethical leadership has become a crucial factor for multinational companies (MNCs) in maintaining organizational sustainability and employee welfare. This research aims to analyze the influence of ethical leadership on employee retention in MNCs using a Systematic Literature Review (SLR) approach. The results of the analysis show that ethical leadership acts as a significant predictor in increasing organizational commitment, trust, and job satisfaction, which in turn reduces employee turnover intentions. Additionally, mechanisms such as psychological safety, organizational justice, and job satisfaction were found to be a link between ethical leadership and employee retention. The research also identified contextual factors, including cultural differences and industry challenges, that influence these relationships. These findings provide practical implications for MNCs in formulating effective ethical leadership strategies to increase employee retention in complex and multicultural work environments.